Analysis Of The Audio-Magnetotelluric (AMT) Data Quality Using The Coherence Parameter at Malabar Mountains - Kusuma, Nabila Putri; Rahmawati, Nabilah; Hanifah, Shofie Dzakia; Harja, Asep; Lucki Junursyah, Gusti Muhammad (Universitas Islam Negeri Ar-Raniry, 2024)
Noise recorded during measurements can diminish the quality of AMT data. This can lead to decreased penetration depth and unreliable 1D inversion models. This study aimed to reduce noise and improve data quality by analyzing coherence, curve trend, and skewness. Coherence analysis was performed using robust processing and XPR editing, yielding an average coherence value of 77.5%, an improvement of 10.8% from the raw data. Noise can also alter data dimensionality; hence, skewness analysis was used to determine the effect of distortion on the impedance tensor. Results showed that the 3D dimensionality effect at 6 stations was significantly reduced following coherence and curve trend analyses.